Why do consumers perpetrate fraudulent behaviors in insurance? - Ribeiro, Raquel (Crime, law and social change, 2020)
Insurance fraud is an increasing problem with major financial, societal and humanitarian impact. Several disciplines have attempted to explain fraudulent behaviors in insurance perpetrated by consumers from economics to criminology and social psychology. Drawing on data from a national survey in Portugal, this study analyzed the levels of acceptance of and justifications underlying fraudulent behavior related to automobile, workplace accidents, and health insurance. Cluster analysis revealed two main groups of respondents with divergent positions: those who consider fraud unacceptable and unjustifiable vs. those who consider it normal and justifiable. A third cluster of respondents consider fraud generally unacceptable but justifiable when it attempts to restore justice. Results are discussed considering the importance of contractual, individual, relational as well as cultural and macrosocial factors in dealing with the complexity of consumers’ unethical behavior. We argue for an integrated approach to research and prevention of consumer insurance fraud.